Case report: Suture associated corneal abscess three years after cataract surgery - Wani M.G (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2014)
We describe a case of corneal abscess presenting three years after uneventful cataract extraction with posterior chamber lens implantation through a limbal incision secured with three sutures placed in the clear cornea. After removing the abscess, a loose 10/0 nylon suture was found at the base of an ulcer. The suture was removed and a scraping taken from the base of the ulcer after which the patient was started on topical antibiotics and cycloplegics. Results of Gram stain microscopy were negative. After one month follow up, the ulcer had healed without perforation leaving a deep depression on the cornea. Risk factors and bacteriology of suture related corneal abscess are discussed and suture associated complications of cataract surgery are reviewed.